Ferroptosis-protective membrane domains in quiescence - Amalia H. Megarioti; Bianca M. Esch; Alexandros Athanasopoulos; Dimitrios Koulouris; Manousos Makridakis; Vasiliki Lygirou; Martina Samiotaki; Jerome Zoidakis; Vicky Sophianopoulou; Bruno André; Florian Fröhlich; Christos Gournas (Cell Reports, 2023)
Summary: Quiescence is a common cellular state, required for stem cell maintenance and microorganismal survival under stress conditions or starvation. However, the mechanisms promoting quiescence maintenance remain poorly known. Plasma membrane components segregate into distinct microdomains, yet the role of this compartmentalization in quiescence remains unexplored. Here, we show that flavodoxin-like proteins (FLPs), ubiquinone reductases of the yeast eisosome membrane compartment, protect quiescent cells from lipid peroxidation and ferroptosis. Eisosomes and FLPs expand specifically in respiratory-active quiescent cells, and mutants lacking either show accelerated aging and defective quiescence maintenance and accumulate peroxidized phospholipids with monounsaturated or polyunsaturated fatty acids (PUFAs). FLPs are essential for the extramitochondrial regeneration of the lipophilic antioxidant ubiquinol. FLPs, alongside the Gpx1/2/3 glutathione peroxidases, prevent iron-driven, PUFA-dependent ferroptotic cell death. Our work describes ferroptosis-protective mechanisms in yeast and introduces plasma membrane compartmentalization as an important factor in the long-term survival of quiescent cells.